Different types of mucormycosis: case series - Jaju, Madhusudan R.; Sagar, R. Vidya; Srivastav, Shashank Kumar; Singh, Ranbeer; Kumar, K. Vijay; Faisal, Mohammed (International Journal of Research in Medical Sciences, 2020)
Mucormycosis is the third invasive mycosis in order of importance after candidiasis and aspergillosis and is caused by fungi of the class Zygomycetes. The most important species causing Mucormycosis is Rhizopus arrhizus (oryzae). Identification of the agents responsible for mucormycosis is based on macroscopic and microscopic morphological criteria, carbohydrate assimilation and the maximum temperature compatible with its growth. The incidence of mucormycosis is approximately 1.7 cases per 1000 000 inhabitants per year. Clinical diagnosis of mucormycosis is difficult, and is often made at a late stage of the disease or post-mortem. We present here a series of five cases of different types of mucormycosis that were reported in our hospital till date. Of which three patients had good recovery and other two had a fatal outcome. Treatment of mucormycosis requires a rapid diagnosis, correction of predisposing factors, surgical resection or debridement as part of source control-and appropriate anti-fungal therapy. Liposomal amphotericin B is the drug of choice for this condition. The overall rate of mortality of mucormycosis is approximately 40%.